Feeling Connected to the Cause: The Role of Perceived Social Distance on Cause Involvement and Consumer Response to CSR Communication. (March 2022) - Heo, Yujin; Choi, Chang-Won; Overton, Holly; K. Kim, Joon; Zhang, Nanlan
Despite the importance of companies' corporate social responsibility (CSR) efforts to support the issue of empowering women, little is known about which communication strategies are effective for a successful CSR initiative. This research investigated how CSR messages influences consumer evaluations of a CSR activity supporting women's empowerment via consumers' cause involvement by conducting two experimental studies. In Study 1, a 2 (CSR message type: in-group vs. out-group) × 2 (gender: female vs. male) online factorial experiment ( n = 140) was employed. The results indicate that consumers evaluated the CSR activity more positively when they were exposed to an in-group message than an out-group message. To increase the validity and explain the process by which CSR message types influence consumer evaluations of a CSR activity, Study 2 was conducted. Psychological distance manipulated by CSR campaign messages increased an individual's level of cause involvement, which in turn influenced the individuals' response to the CSR activities. Implications are discussed.